TEACHING MATHEMATICS IN BASIC EDUCATION THROUGH PROBLEM SOLVING - Santos Carvalho, Regivaldo (Revista Gênero e Interdisciplinaridade, 2023)
Even today, since the first school years, most of the time in Mathematics classes, it is observed that students learn to do math (algorithms), with predetermined rules and steps, presented on the blackboard and in textbooks, at which they have to follow without, however, previously reasoning why they are doing that, or even without having the possibility of developing their own method to solve mathematical problems. This mechanization of the teaching-learning process of mathematical concepts causes students to lack understanding and interest in the subject. On the other hand, when using the resolution of challenging problem situations, applying examples from the school context, it helps the development of students’ autonomous reasoning. In this context, the present study will focus on the importance of solving problem situations in teaching Mathematics in Basic Education, using bibliographic data as a research method. Furthermore, the main objective of the research is to discuss the importance of solving problem situations in teaching Mathematics in Basic Education. Furthermore, it is worth highlighting that research highlights the role of the teacher as a stimulator and mediator of the hypotheses raised by students, enabling them to develop logical reasoning capacity, understanding the importance of mathematical concepts for their day-to-day lives.